Pengaruh Perkembangan Kendaraan Listrik Terhadap Industri Otomotif Pada Era Society 5.0 - Danang Rahmat Bachtiar; Harits Ar Rosyid; Khurin Nabila (Universitas Ngeri Malang, 2022)
The development of electric vehicles has become the focus of the automotive industry in the era of society 5.0. This article aims to explore the influence of the development of electric vehicles on the automotive industry in the era of society 5.0. The research method used is secondary research by applying a quantitative approach. The results of the study show that the development of electric vehicles has a positive impact on the automotive industry, with increasing demand for and investment in electric vehicles. The development of increasingly sophisticated electric vehicles will open up new opportunities for vehicle manufacturers to increase competitiveness. Vehicle manufacturers can develop electric vehicles that are more energy efficient, more environmentally friendly, and more innovative. However, there are also challenges such as technological and regulatory limitations that can hinder the growth of the automotive industry in the era of society 5.0. The development of electric vehicles has great potential to change the automotive industry in the era of society 5.0 and there needs to be collaborative efforts between industry, government, and society to take advantage of opportunities from the development of electric vehicles. Perkembangan kendaraan listrik telah menjadi fokus utama industri otomotif pada era society 5.0. Artikel ini bertujuan untuk mengeksplorasi pengaruh dari perkembangan kendaraan listrik terhadap industri otomotif pada era society 5.0. Metode penelitian yang digunakan adalah penelitian sekunder dengan menerapkan pendekatan kuantitatif. Hasil penelitian menunjukkan bahwa perkembangan kendaraan listrik berdampak positif terhadap industri otomotif, dengan meningkatnya permintaan dan investasi pada kendaraan listrik. Dengan perkembangan kendaraan listrik yang semakin canggih akan membuka peluang baru bagi para produsen kendaraan untuk meningkatkan daya saing. Para produsen kendaraan dapat mengembangkan kendaraan listrik yang lebih hemat energi, lebih ramah lingkungan, dan lebih inovatif. Namun, terdapat juga tantangan seperti keterbatasan teknologi dan regulasi yang dapat menghambat pertumbuhan industri otomotif pada era society 5.0. Perkembangan kendaraan listrik memiliki potensi besar untuk mengubah industri otomotif pada era society 5.0 dan perlu adanya upaya kolaborasi antara industri, pemerintah, dan masyarakat untuk memanfaatkan peluang dari perkembangan kendaraan listrik.